Study of a hospital outbreak by enlarged SHV-5 spectrum beta-lactamase producing Salmonella typhimurium - Del Pozo, Liliana (2006)
Background: An ESBL Salmonella typhimurium outbreak occurred at San Bartolome hospital from February 17 through March 16, 2001. Objectives: To identify the mechanism involved in Salmonella typhimurium spread and genetic characterization of beta-lactamase resistance associated genes. Design: Clinical-bacteriologic retrospective study. Setting: San Bartolomé Mother Child Teaching National Hospital. Biologic materials: Bacterial isolations from lactating patients. Interventions: The genetic diversity was characterized from five bacterial isolates from infants admitted to the pediatric units, using REP-PCR and plasmid fingerprinting. We previously characterized the antimicrobial resistance, determining the presence of ESBL by the double disc diffusion method and the variant was identified by sequencing the gen blashv . Main outcome measures: Salmonella typhimurium genotypes, plasmids and beta-lactamase presence. Results: We found two different genotypes among the Salmonella typhimurium isolates; the index case (susceptible) showed a different genotype and the other isolates coming from hospitalized children were resistant. One of the S. typhimurium plasmids had a heavier molecular weight than K. pneumoniae’s but as heavy as the hospital acquired E. coli isolates plasmids. We found the ESBL SHV-5 in both S. typhimurium y E. coli isolates. Conclusions: This report suggests that the bacteria spread among infants could be facilitated by many factors playing different roles in the genetic material transfer responsible of the microbial resistance.